Determinants of performance cluster: Case applied to furniture industry in Barranquilla, Colombia - López Jiménez, Jael (2016)
This paper estimates the influence of some determinants of success on the performance of a cluster. This was aimed to better understand the cluster as a strategic tool for local economic development. It focuses on the identification of a set of key factors that, according to the literature, can influence the performance of clusters, and how the same factors influence the furniture cluster of Barranquilla. A questionnaire was applied to 54 companies belonging to the furniture cluster, according to the databases provided by the Cámara de Comercio de Barranquilla, Colombia Inn. As a result, the factors quality, location, best practices, business cooperation and the existence of a positive local environment, have a high and positive relationship with the performance. Finally a number of recommendations are proposed to improve cluster development, in particular, and similar initiatives in general.